1981
DOI: 10.1111/j.1745-4514.1981.tb00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Yam Starches

Abstract: Starch from tubers of Dioscorea alata, Dioscorea cayenensis, Dioscorea dumetorum, and Dioscorea rotundata was isolated and some of the important characteristics determined. Amylose and amylopectin fractions were obtained by aqueous leaching technique. All the starches appeared to have definite but minor differences in iodine binding capacity, swelling power, solubility, intrinsic viscosity, and amylose/amylopectin ratio. Brabender amylogram of each starch showed no distinct peak viscosity, and the general amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 14 publications
11
56
2
Order By: Relevance
“…The internal lipids of cereal starches are predominantly monoacyf lipids, with the major component being Iysophospholipids (of which Iysophosphatidylcholine is the major component) and free fatty acids (Hargin & Morrison, 1980;Morrison, 1981 (Morrison, 1981), whereas prolonged extraction with hot aqueous alcoholic solvent systems (Morrison, 1981) or disruption of the granularslructure by acid hydrolysis (Goshimaetat., 1985)isrequiredfortheefficientremoval6f bound lipids. The amount of total starch lipids (surface and bound) has been found to be in the range of 0.7-1.2% in cereals (Morrison & Milligan, 1982;Vasanthan & Hoover, 1992b;Takahashi & Seib, (1988), 0.01-0.87% in legumes (Hoover & Sosulski, 1985), and 0.08-0.19% in tubers and roots (Vasanthan & Hoover, 1992b;Emiola & Delarosa, 1981;Goshima etat., 1985). Zobel (1988a) suggested that lipids in starches may be responsible for effecting an amylose separation within the granule.…”
Section: Swinkelsmentioning
confidence: 99%
“…The internal lipids of cereal starches are predominantly monoacyf lipids, with the major component being Iysophospholipids (of which Iysophosphatidylcholine is the major component) and free fatty acids (Hargin & Morrison, 1980;Morrison, 1981 (Morrison, 1981), whereas prolonged extraction with hot aqueous alcoholic solvent systems (Morrison, 1981) or disruption of the granularslructure by acid hydrolysis (Goshimaetat., 1985)isrequiredfortheefficientremoval6f bound lipids. The amount of total starch lipids (surface and bound) has been found to be in the range of 0.7-1.2% in cereals (Morrison & Milligan, 1982;Vasanthan & Hoover, 1992b;Takahashi & Seib, (1988), 0.01-0.87% in legumes (Hoover & Sosulski, 1985), and 0.08-0.19% in tubers and roots (Vasanthan & Hoover, 1992b;Emiola & Delarosa, 1981;Goshima etat., 1985). Zobel (1988a) suggested that lipids in starches may be responsible for effecting an amylose separation within the granule.…”
Section: Swinkelsmentioning
confidence: 99%
“…The internal lipids mostly are monoacylglycerides, with the major components being lysophospholipids and free fatty acids (Hargin and Morrison, 1980;Morrison, 1981;Vasanthan and Hoover, 1992). Total starch lipids (surface plus internal) have been found to be generally in the range of0.7-1.2% in cereals (Morrison and Milligan, 1982;Takahashi and Seib, 1988;Vasanthan and Hoover, 1992), 0.01-0.87% in legumes (Table 2-3) and 0.08-0.19% in tubers and roots (Emiola and Delarosa, 1981;Goshima et al, 1985;Vasanthan and Hoover, 1992).…”
Section: Lipidsmentioning
confidence: 99%
“…The variation in their physicochemical properties as well as the morphological difference in size and shape of starch granules ( Fig. 1) has been attributed to the difference in the botanical sources as well as the biosynthesis of the starch granules and the physiology of the plant [6][7][8][9][10]. Dioscorea starch granules have been shown to vary in shape from spherical, oval to polygonal shape depending on the species with granule size ranging from 2 to 50 mm [11].…”
Section: Yamsmentioning
confidence: 99%
“…When converted into pastes and used as a binding agent in tablet formulation, sweet potato starch paste was found to produce tablets with higher bond strength than corn starch [38] indicating its potential usefulness as alternative binding agent to produce tablets with particular tableting and mechanical properties. [6]; (c) D. dumetorum [6]; (d) D. alata [6]; (e) D. esculenta [7]; (f) D. cayenensis [9]; (g) D. nipponica [10]; (h) D. bulbifera [10]; (i) D. septemloba [10].…”
Section: Sweet Potato (Ipomoea Batatas)mentioning
confidence: 99%
See 1 more Smart Citation